Efek Gliserin sebagai Humectan Terhadap Sifat Fisik dan Stabilitas Vitamin C dalam Sabun Padat - Sukmawati, Anita; Laeha, Ms. Nur-ainee; Suprapto, Suprapto (Universitas Muhammadiyah Surakarta, 2017)
Glycerin is a humectant that is used frequently for cosmetics, especially in soaps. This study was conducted to determine the influence glycerin on the physical properties of glycerin soap including pH, soap hardness, foam stability, and also on the stability of vitamin C in the soap during 8 weeks storage. Vitamin C is formulated in soap with various concentrations of glycerin i.e 5%, 10% and 20%. Evaluation of the soap preparations include a pH test, soap hardness, foam stability test and evaluation on the stability of vitamin C for 8 weeks and the results obtained will be statistically analyzed using SPSS version 16 for windows by the Kruskal-Wallis method on the results test of pH and soap hardness, and using one way ANOVA method for evaluating foam stability. The results showed that glycerol did not significant influence on the pH value of soap with a significance value of P = 0.26> 0.05, while increasing the concentration of glycerin in the soap increased products softness. The foam stability testing showed that the difference in the concentration of glycerin on soap had no significant effect on improving the stability of foam. The best foam stability was found in vitamin C soap containing glycerine 10%. Glycerin also affected the stability of vitamin C in the soap. The stability of vitamin C is increased related to the increasing glycerin concentration in soap as demonstrated in formula III, which contained 20% glycerin and had 49.48% reducing in level of vitamin C, while the soap containing glycerine 5 % and 10%, had decreased 77.98% and 60.67% respectively in level of vitamin C during the storage period of 8 weeks.